The Effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover Ratio on Return on Assets - Akbar, Muhammad; Fauziah, Citra (International Journal Labs, 2025)
This study aims to examine and analyze the influence of financial ratios, specifically the Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO), on Return on Assets (ROA) in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was employed, using a purposive sampling method based on specific criteria. From a population of 96 companies, 14 companies met the criteria over a five-year period, resulting in a total of 70 observations. The study utilized secondary data derived from the companies’ annual financial statements. Data analysis was conducted using EViews 12 software with a panel data regression model. The results of the analysis indicate that the Current Ratio (CR) has no significant effect on Return on Assets (ROA), while the Debt to Equity Ratio (DER) has a significant negative effect, and the Total Asset Turnover (TATO) has a significant positive effect on ROA. These findings suggest that financial management in the property and real estate sector should focus on optimizing asset utilization and capital structure to enhance corporate profitability.